Sentinel Lymph Node Biopsy in a Resource Limited Setting: A Retrospective Comparison of Sentinel Lymph Node Biopsy before and after the introduction of SentiMag at an Academic Breast Unit - Yousef, Mazen Mohamed S (Division of General Surgery, 2023)
Background: Sentinel lymph node biopsy (SLNB) is performed for the staging and prognostication of breast cancer in cases with a clinically and radiologically negative axilla. Using blue dye and a radioactive colloid injection is considered the gold standard for SLNB. This study aims to evaluate the SLNB outcomes before and after the introduction of SentiMag at an academic breast unit Methods: A retrospective cohort study was performed comparing SLNBs done from (1 January 2017 to 31 December 2017) and (1 January 2018 to 31 December 2018). During 2017 all SLNBs were done with a nuclear medicine technique and in 2018 the Sentimag system was used. Results: There was no difference between the 2 groups comparing age, T-stage, size of tumour, grade of tumour and molecular status. The only statistically significant difference found was more higher-grade tumours in the group where a nuclear medicine technique was used (2017) p=0.04. There was no difference in the type of surgery performed comparing mastectomy and breast conserving surgery rates between the 2 groups. There was an 11% increase in the number of patients who had a SLNB done with the SentiMag technique (2018). In 2017 42% (58/139) had a SLNB and in 2018 53% (59/112) had a SLNB Conclusion: This result demonstrates the feasibility of the magnetic technique for SLNB in a resource constrained low- and middle-income country. This new method has none of the disadvantages of the standard technique and is promising as a safe and effective alternative in the absence of nuclear medicine facilities.